Geriatrics and Ageing in the Soviet Union Medical, Political and Social Contexts - Scarborough, Isaac McKean; Grant, Susan (Bloomsbury Academic, 2022)
The first comprehensive exploration of ageing in the Soviet Union which places it in a domestic and international context.